Ketertarikan Spesies Lalat Buah terhadap Atraktan Minyak Atsiri Selasih (Ocimum basilicum) pada Pertanaman Tomat (Solanum lycopersicum) di Kecamatan Sukasada Kabupaten Buleleng - Mancika, Ni Made Juliana Dewi; Wijaya, I Nyoman; Darmiati, Ni Nengah (Agrotrop : Journal on Agriculture Science; Vol 14 No 1 (2024), 2024)
Interest of Fruit Fly Species on Basil Essential Oil ( Ocimum basilicum ) Attractants on Tomato ( Solanum lycopersicum ) Planting in Sukasada District, Buleleng Regency . Fruit flies ( Bactrocera sp .) are important pests in fruit cultivation in Indonesia, including tomato plants. One method that can be used to control fruit flies is attractant traps. This study aims to determine the species, sex, and abundance of fruit flies trapped by basil essential oil attractants in tomato plantations in Sukasada District, Buleleng Regency. The research began with the manufacture of basil essential oil using the steam distillation method, followed by the manufacture and installation of attractant traps, identification of the morphology of fruit flies, and calculating the abundance of fruit fly species. The results showed that there were two trapped fruit fly species, namely Bactrocera carambolae and Bactrocera dorsalis with 100% male sex. The species with the highest abundance was Bactrocera carambolae (61.79%) followed by Bactrocera dorsalis (38.21%). More fruit flies were trapped in the generative phase of tomato plants (83.74%) than in the vegetative phase of tomato plants (16.26%).